Optimalisasi Pencahayaan Alami dan Buatan pada Laboratorium Komputer Menggunakan Simulasi Dialux - Rahmayanti, Rahmayanti; Mutmainnah, Nur; Musa, Harun (Program Studi Teknik Arsitektur, Fakultas Teknik, Universitas Ichsan Gorontalo, 2025)
This research examines the optimization of natural and artificial lighting in the ABG Computer Laboratory using Dialux simulation. The study aims to evaluate daylight performance based on window configuration, investigate the causes of deviation between simulation results and on-site illuminance measurements, and develop an artificial lighting layout that fulfills visual comfort standards for computer-based learning spaces. The initial daylight simulation revealed that 59.8% of the total floor area achieved illumination levels of ≥300 lux; however, field measurements showed substantially lower illuminance due to shading from dense vegetation in front of the façade, leading to uneven light distribution across the room. The artificial lighting simulation using 50W 6500K LED luminaires successfully provided uniform illuminance of ≥500 lux throughout the working plane. These findings confirm that a hybrid lighting system—integrating optimized daylight and artificial lighting—is the most reliable and energy-efficient solution for computer-oriented educational environments.